Understanding divergent domestication traits from the whole-genome sequencing of swamp- and river-buffalo populations - Xier Luo; Yu Zhou; Bing Zhang; Yi Zhang; Xiaobo Wang; Tong Feng; Zhipeng Li; Kuiqing Cui; Zhiqiang Wang; Chan Luo; Hui Li; Yanfei Deng; et al. (Oxford University Press, 2020)
Domesticated buffaloes have been integral to rice-paddy agro-ecosystems for millennia, yet relatively little is known about the buffalo genomics. Here, we sequenced and assembled reference genomes for both swamp and river buffaloes and we re-sequenced 230 individuals (132 swamp buffaloes and 98 river buffaloes) sampled from across Asia and Europe. Beyond the many actionable insights that our study revealed about the domestication, basic physiology and breeding of buffalo, we made the striking discovery that the divergent domestication traits between swamp and river buffaloes can be explained with recent selections of genes on social behavior, digestion metabolism, strengths and milk production.